PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE MENGGUNAKAN METODE CERITA UNTUK MENINGKATKAN HASIL BELAJAR AGAMA KRISTEN SISWA KELAS III SD NEGERI 043935 SIMPANG KATEPUL KABUPATEN KARO - JADI MULIA BR TARIGAN (LP2MTBM MAKARIOZ, 2019)
This study aims to determine the increase in student learning outcomes and activities in the subject matter of loving others after the implementation of the value clarification technique learning model using the story method in class III 043935 Public Elementary School Katepul Intersection in Karo Regency 2017/2018 academic year. This research is a classroom action research in two cycles. The research subjects were third grade students of SD Negeri 043935, Katepul Intersection, Karo Regency, 2017/2018 learning year, totaling 16 students. Student learning outcomes data obtained through tests while student learning activity data obtained through observation sheets. Data is processed by being described as a percentage using the minimum completeness criteria (KKM) reference. The results of the study show; 1) completeness of student learning outcomes increases by applying the value clarification technique learning model using the formative I story method shows an average of 73 with 69% classical completeness and formative II shows an average of 77 with 88% classical completeness or reaches classical completeness and occurs 19% increase; 2) student learning activities increase after the implementation of the value clarification learning model using the story method with the activities of students on average according to observers in Cycle I, among others, reading and understanding 57.12%, doing assignments 52.88%, group discussions 53.18 %, asking teachers 63.94%, and presentations 54.09%. While the activities of students on average according to observations in Cycle II include reading and understanding 86.21%, doing assignments 86.82%, discussing groups of 88.48%, asking teachers 88.94%, and presentations 89.09%.